MicroRNA-486-5p suppresses inflammatory response by targeting FOXO1 in MSU-treated macrophages - Jianguo Hu; Cheng Jin; Li Fang; Yao Lu; Yanying Wu; Xiangfeng Xu; Simei Sun (Taylor & Francis Group, 2022)
Gouty arthritis (GA) is mainly caused by the precipitation of monosodium urate (MSU) crystals in the joint. Recently, different regulatory roles of microRNAs (miRNAs) in arthritis have been widely verified. Nevertheless, the specific function of microRNA-486-5p (miR-486-5p) in GA is still unclear. GA cell models in vitro were established by the treatment of 250 μg/mL MSU crystals into THP-1 cells or J774A.1 cells. Then, the accumulation of tumor necrosis factor (TNF)-α, interleukin (IL)-8, and IL-β was estimated by ELISA. The mRNA levels of TNF-α, IL-8, and IL-β were measured through RT-qPCR. The protein level of forkhead box protein O1 (FOXO1) was tested via western blot. Furthermore, the interplay of miR-486-5p and FOXO1 was evaluated via the luciferase reporter assay. In this study, MSU treatment successfully stimulated the inflammatory response in macrophage cells. MiR-486-5p downregulation was observed in THP-1 and J774A.1 cells treated with MSU, and its upregulation markedly decreased the concentration and mRNA levels of TNF-α, IL-8, and IL-β. Furthermore, FOXO1 was demonstrated to be negatively modulated by miR-486-5p. The rescue assay indicated that overexpressing FOXO1 reversed the effects of overexpressing miR-486-5p on inflammatory cytokines. Overall, this study proves that miR-486-5p inhibits GA inflammatory response via modulating FOXO1.